Performance the Malcolm Baldrige on State Electricity Company (PLN) in Indonesia - Oktrivina, D. S. Amelia; Suroso, Sugeng; Purwoko, Bambang; Widyastuti, Tri (International Journal of Economics and Financial Issues, 2017)
The purpose of this study is to examine and analyze the influence of internal control over corporate governance, internal control influence on corporate performance, the influence of corporate governance on corporate performance.. The research method uses are analytical descriptive and exploratory. Results of the study are: internal control has positive effect on the corporate governance, internal control has positive effect on the Malcolm Baldrige performance, corporate governance has positive effect on the Malcolm Baldrige performance. Keywords: Internal Control, Corporate Governance, Malcom Baldrige Performance JEL Classifications: L80, G34